(untitled) (GEOgraphia, 2025)
The COVID-19 pandemic has profoundly affected the Higher Education community. Suddenly, universities worldwide had to shift from face-to-face lectures to online teaching and learning, and students faced challenges, that created anxieties about their future careers and mobility plans. This research questions the impacts of the pandemic on international student mobility flows to Portugal and the student’s lived experiences during the pandemic. To this end, the study adopted a mixed-method design, combining official data and primary data from an online survey questionnaire and semi-structured interviews with International Students (IS). Although it is not possible to foresee the effects of the pandemic on the internationalization of Portuguese Higher Education Institutions (HEI), our findings indicate that Portugal tends to remain an attractive country for international students, especially for those coming from the former colonies. Furthermore, the student´s reports of their experiences during the health crisis, demonstrate different levels of vulnerability across gender, geographical origin and level of education attended.